Phase structure dependence of magnetic behaviour in iron oxide nanorods. (5th January 2020) - Hu, Hailong; Yuan, Yuan; Lim, Sean; Wang, Chun H.
Abstract: Magnetic properties in iron oxide nanorods, which have many applications in biomedicine, catalysts, and magnetic resonance imaging, depend on their manufacturing processes and phase structures. Although various structures on iron oxide have been reported, there is a lack of understanding of the property-phase relationship for iron oxide nanorods. Herein, we report an economical route to synthesize iron oxide nanorods with alterable phases including akaganeite (β-FeOOH), hematite (α-Fe2 O3 ), maghemite (γ-Fe2 O3 ), and magnetite (Fe3 O4 ). Detailed analysis of the synthesis methods, phase structures and magnetic properties of iron oxide nanorods identified the relationship between the phase structure and the magnetic properties. The findings reported in this paper show that the excellent tunability of magnetism in iron oxide nanorods will pave the way for selecting the best manufacturing process to meet the desired properties of specific applications such as carriers in biomedicine, magnetic recording materials, gas sensors and catalysts applications. Graphical abstract: Image 1 Highlights: An economical route is developed to synthesize iron oxide nanorods with alterable phases. The property-phase relationship is identified in iron oxide nanorods. The excellent tunability of magnetism has been achieved in iron oxide nanorods.